Determinants of epigenetic resistance to HDAC inhibitors in dystrophic fibro‐adipogenic progenitors. (4th April 2022) - Consalvi, Silvia; Tucciarone, Luca; Macrì, Elisa; De Bardi, Marco; Picozza, Mario; Salvatori, Illari; Renzini, Alessandra; Valente, Sergio; Mai, Antonello; Moresi, Viviana; Puri, Pier Lorenzo
Abstract: Pharmacological treatment of Duchenne muscular dystrophy (DMD) with histone deacetylase inhibitors (HDACi) is currently being tested in clinical trials; however, pre‐clinical studies indicated that the beneficial effects of HDACi are restricted to early stages of disease. We show that FAPs from late‐stage mdx mice exhibit aberrant HDAC activity and genome‐wide alterations of histone acetylation that are not fully reversed by HDACi. In particular, combinatorial H3K27 and/or H3K9/14 hypo‐acetylation at promoters of genes required for cell cycle activation and progression, as well as glycolysis, are associated with their downregulation in late‐stage mdx FAPs. These alterations could not be reversed by HDACi, due to a general resistance to HDACi‐induced H3K9/14 hyperacetylation. Conversely, H3K9/14 hyper‐acetylation at promoters of Senescence Associated Secretory Phenotype (SASP) genes is associated with their upregulation in late‐stage mdx FAPs; however, HDACi could reduce promoter acetylation and blunt SASP gene activation. These data reveal that during DMD progression FAPs develop disease‐associated features reminiscent of cellular senescence, through epigenetically distinct and pharmacologically dissociable events. They also indicate that HDACi might retain anti‐fibrotic effects at late stages of DMD. SYNOPSIS: Progressive increase of HDAC activity in Fibro‐adipogenic progenitors from Duchenne Muscular Dystrophy model mice leads to altered histone acetylation profiles associated with senescence at late disease stages that are not fully reversed by HDAC inhibitors. HDAC activity increases in FAPs of muscles from mdx mice at late stages of disease progression. FAPs of late stage mdx muscles exhibit altered profiles of histone acetylation and develop features of senescence. HDAC inhibitors fail to reverse cell cycle arrest and glycolysis In FAPs of late stage mdx muscles. HDAC inhibitors inhibit activation of SASP genes in FAPs of late stage mdx muscles. Abstract : Progressive increase of HDAC activity in Fibro‐adipogenic progenitors from Duchenne Muscular Dystrophy model mice leads to altered histone acetylation profiles associated with senescence at late disease stages that are not fully reversed by HDAC inhibitors.